A closer look at Santiago de Compostela's pilgrims through the lens of motivations - Amaro, Suzanne (2018)
This study aims to identify pilgrims’ motivations to undertake the Camiño de Santiago and examine differences regarding socio demographics and other characteristics. An online questionnaire was used to collect data from pilgrims that had travelled the Camiño de Santiago. A total of 1,140 valid responses was collected from 45 different nationalities. The results indicate that pilgrims are mostly motivated by spiritual aspects, by wanting new experiences and for the nature and sports experience. Interestingly, religious motivations are the least important. The study also found that motivations differ according to several factors such as gender, nationality and the way the pilgrims undertook their journey. The findings of this study offer a better understanding of modern pilgrims, providing useful insights to stakeholders.